2007
DOI: 10.1007/s12010-007-9105-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of tocopherol concentration process from soybean oil deodorized distillate using response surface methodology

Abstract: Soybean oil deodorized distillate is a product derived from the refining process and it is rich in high value-added products. The recovery of these unsaponifiable fractions is of great commercial interest, because of the fact that in many cases, the "valuable products" have vitamin activities such as tocopherols (vitamin E), as well as anticarcinogenic properties such as sterols. Molecular distillation has large potential to be used in order to concentrate tocopherols, as it uses very low temperatures owing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…It is reported that most of the lost chemicals were removed to deodorizer distillate (Shimada et al, 2000). Other than temperature, vacuum is also an important factor that affects the removal of impurities such as tocopherol in the soybean oil refining process (Ramamurthi and McCurdy, 1993;Ito et al, 2007). We have found that reducing the operational temperatures in most refining steps could effectively remove undesirable impurities and prevent the loss of bioactive compounds using the same processing times and vacuum pressures, thus preserving the nutritional value of tea seed oil.…”
Section: Discussionmentioning
confidence: 94%
“…It is reported that most of the lost chemicals were removed to deodorizer distillate (Shimada et al, 2000). Other than temperature, vacuum is also an important factor that affects the removal of impurities such as tocopherol in the soybean oil refining process (Ramamurthi and McCurdy, 1993;Ito et al, 2007). We have found that reducing the operational temperatures in most refining steps could effectively remove undesirable impurities and prevent the loss of bioactive compounds using the same processing times and vacuum pressures, thus preserving the nutritional value of tea seed oil.…”
Section: Discussionmentioning
confidence: 94%
“…Vitamin E is an essential nutrient derived from various crops, such as barley, wheat, and soybean (Hakkarainen et al, 1984;Hall and Laidman, 1968;Ito et al, 2007). Vitamin E has several isomers, including ␣-, ␤-, ␥-, and ␦-tocopherols (Leth and Sondergaard, 1977), the activity and bioavailability of which vary depending on their structures and physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, numerous studies focused on obtaining mixed tocopherol from deodorized distillate (Hiromori et al, 2016;Ito et al, 2007;Zhou et al, 2009). Few studies paid attention to the separation and purification of γ-tocopherol.…”
Section: Introductionmentioning
confidence: 99%